1999
DOI: 10.1006/brln.1999.2081
|View full text |Cite
|
Sign up to set email alerts
|

The Mass/Count Distinction: Evidence from On-Line Psycholinguistic Performance

Abstract: Under the hypothesis that the mass/count distinction in English is marked by a monovalent lexical feature, this article investigates whether features, lexical or morphosyntactic, play a role in simple lexical decision. Research findings have yet to settle how many features are accessed during lexical decision and to what extent morphosyntactic features are computed out of context. We used two on-line lexical decision experiments (simple and morphosyntactic priming). Results show that the lexical feature ''mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
37
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 5 publications
6
37
0
Order By: Relevance
“…Gillon, Kehayia, and Taler (1999) found that mass nouns were processed more slowly than count nouns in a simple lexical decision task, and that both noun types yielded faster reaction times (RTs) when primed by a determiner with which they formed a grammatical combination. These results were taken to indicate that there exists a semantic feature [mass] ([M]), which is accessed when the word is recognised.…”
Section: Introductionmentioning
confidence: 99%
“…Gillon, Kehayia, and Taler (1999) found that mass nouns were processed more slowly than count nouns in a simple lexical decision task, and that both noun types yielded faster reaction times (RTs) when primed by a determiner with which they formed a grammatical combination. These results were taken to indicate that there exists a semantic feature [mass] ([M]), which is accessed when the word is recognised.…”
Section: Introductionmentioning
confidence: 99%
“…They conclude that the count/mass distinction has primarily a syntactic basis. Finally, Gillon, Kehayia, and Taler (1999), using a simple and a primed lexical decision task, showed no differences between ''non-atomic'' mass nouns like oil and sugar (which are divisible: if you divide oil in two, you still have oil) and count nouns. ''Atomic'' mass nouns, like furniture and money, on the other hand, took longer to recognize than count nouns (see also Wiese & Piñ ango, 2001.…”
Section: The Count Noun/mass Noun Distinctionmentioning
confidence: 92%
“…We assume that for English adults some noun senses are basically count (pear, biscuit) and others basically mass (beer, pudding). Whatever the facts are from language typology (e.g., Krifka, 1995), it is difficult to maintain that the mass interpretation is always the default in adult comprehension (see, e.g., Gillon et al, 1999;Steinhauer et al, 2001, for evidence). Our corpus search (see below) also indicates that there was a strong bias for either a count or a mass interpretation for the nouns tested in the experiments.…”
Section: Polysemy and The Count/mass Distinctionmentioning
confidence: 99%
“…Theoretical linguistic accounts describe mass nouns as formally simpler than count nouns (Borer, 2005;Chierchia, 2010;Krifka, 1995), yet experimental literature does not provide consistent evidence in this sense. Some lexical decision studies reported longer response times associated to the processing of mass nouns (Gillon et al, 1999;Mondini et al, 2009), whereas some others did not find any difference (Mondini et al, 2008;Franzon et al, 2016). A preference for countability is reported in studies on acquisition (Barner & Snedeker, 2005;Gathercole, 1985) and in neuropsychological studies Fieder et al, 2014;.…”
Section: Introductionmentioning
confidence: 99%